2016
DOI: 10.18178/ijlll.2016.2.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Students Engagement in an Online Student Question-Generation Activity towards Their Learning Motivation

Abstract: The purpose of this study is to look into and develop a better understanding on how students are motivated to learn through the tasks of creating their own learning content. In this study, students are exposed to question-generation activity, which employed Peer Wise as a platforma web-based application that allows students to create, answer and share multiple choice questions. A self-report instrument were used to measure students motivational construct of intrinsic goal orientation, extrinsic goal orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Finally, as Sohrabi and Iraj (2016) argued, the challenges of the flipped learning model include: how to successfully apply it in higher education; how to redesign college courses to dedicate in-class time to student-centered activities; and how the designed activities would help students better learn the course content. Instructors in higher education should come up with a variety of activities to incorporate theories, pedagogies, and technologies that are built to enhance student learning (Sabri, Khalid, & Li, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as Sohrabi and Iraj (2016) argued, the challenges of the flipped learning model include: how to successfully apply it in higher education; how to redesign college courses to dedicate in-class time to student-centered activities; and how the designed activities would help students better learn the course content. Instructors in higher education should come up with a variety of activities to incorporate theories, pedagogies, and technologies that are built to enhance student learning (Sabri, Khalid, & Li, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…La variabilidad en la procedencia educativa destaca la necesidad de considerar el contexto institucional en las estrategias de evaluación en línea. Un aporte significativo para la investigación fue el estudio de Masturah (2016) se enfoca en la implementación de evaluaciones formativas en línea, centrándose específicamente en la herramienta "PeerWise", la cual posibilita a los estudiantes la creación y respuesta de preguntas de opción múltiple relacionadas con el contenido del curso. Esta herramienta fomenta el aprendizaje activo y la participación estudiantil, generando un mayor compromiso y una comprensión más profunda de los temas abordados en el curso.…”
Section: Factores Personales Chi2 De Pearson Significanciaunclassified
“…Students were able to utilise and share information, they reported to be more open to ideas from peers and to persevere in their learning goals. Other studies suggested that CLT increased awareness, understanding and collaboration among students, enhanced students’ satisfaction in completing the learning activities and improved their academic performance (Roldán-Álvarez et al, 2020 ; Sabri et al, 2016 ). Given how ICT tools are constantly evolving and increasing in variety in response to learner needs (Mora et al, 2020 ; Wu et al, 2017 ), there is a need to continuously explore the possibilities to facilitate the development of Collaborative learning skills with the use of technologies in the K-12 setting.…”
Section: Literature Reviewmentioning
confidence: 99%